ROTC Warrior of the Pacific, circa 1956 (1956)
Coveted Trophy - Looking over the 'Warrior of the Pacific' trophy recently won by California State Polytechnic college ROTC cadets are left to right, Col. P. A. Loiselle, head of the college military science and tactics department; Peter Mehlschau of Nipomo, top student riflemen; and Julian A. McPhee, president of California State Polytechnic college. A 35-cadet contingent from Cal Poly received the trophy from their showing on the rifle range during summer training at Fort Lewis, Wash. The trophy goes to the ROTC unit in the United States receiving the highest rifle scope at summer camps.